2013
DOI: 10.1074/jbc.m112.440859
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Endogenous Regulation of the Type I Interferon Response by Suppressor of IκB Kinase ϵ (SIKE), a Novel Substrate of TANK-binding Kinase 1 (TBK1)

Abstract: Background: Suppressor of IB kinase ⑀ (SIKE) inhibits a key innate immune effector molecule, TANK-binding kinase 1 (TBK1), through an undefined mechanism. Results: SIKE is a TBK1 substrate. Conclusion: SIKE controls TBK1 activity by acting as a high affinity substrate. Significance: SIKE attenuates phosphorylation of interferon regulatory factor 3 (IRF3) by serving as an alternative, high affinity substrate for TBK1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…Previous studies have reported that SIKE could function as a substrate of TBK1 in in vitro kinetic analyses 18 . Thus, we further examined the potential influence of SIKE phosphorylation status on TBK1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that SIKE could function as a substrate of TBK1 in in vitro kinetic analyses 18 . Thus, we further examined the potential influence of SIKE phosphorylation status on TBK1.…”
Section: Resultsmentioning
confidence: 99%
“…TBK1 and IKKε provided the strongest site‐specific mTOR S2159 phosphorylation. Indeed, the mTOR amino acid sequence surrounding S2159 fits consensus motifs found in defined TBK1 substrates (i.e., IRF3; IRF7; optineurin; suppressor of IKKε [SIKE]; Wild et al , ; Marion et al , ) and bears similarity to an IKKε consensus phosphorylation motif (Fig A; Peters et al , ; Hutti et al , ). At this time, the upstream mTOR T2164 kinase remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…IRF3 phosphorylation at residues Ser-385 and Ser-386 has previously been shown to control its dimerization (23)(24)(25) upon which IRF3 translocates to the nucleus (26), and controls transcriptional regulation of cell survival and proliferation (2,11). In addition to IRF3, several other substrates, i. e., namely cRel, Akt, RalB, SIKE, etc., have been identified that attribute to TBK1 function (7)(8)(9)(27)(28)(29)(30). TBK1 requires phosphorylation at Ser-172 within the kinase domain activation loop to be activated.…”
Section: Introductionmentioning
confidence: 99%